CONCRETE FRACTURE ANALYSIS USING THE CONTINUUM STRONG DISCONTINUITY APPROACH AND THE BOUNDARY ELEMENT METHOD - Peixoto, Rodrigo G.; Ribeiro, Gabriel O.; Pitangueira, Roque L. S. (Revista Interdisciplinar de Pesquisa em Engenharia, 2019)
The implicit formulation of the boundary element method is applied to bi-dimensional problems of material failure involving, sequentially, inelastic dissipation with softening in continuous media, bifurcation and transition between weak and strong discontinuities. The bifurcation condition is defined by the singularity of the localization tensor, also known, for historical reasons, as acoustic tensor. The weak discontinuities are related to strain localization bands of finite width, which become increasingly narrow until to collapse in a surface with discontinuous displacement field, called strong discontinuity surface. To associate such steps to the fracture process in concrete specimens, an isotropic damage (continuum) constitutive model is used to represent the material behaviour in all of them, taking into account the adaptations that come from the strong discontinuity analysis for the post-bifurcation phases. The crack propagation across the domain is done by an automatic cells generation algorithm and, in this context, the fracture process zone in the crack tip became totally represented by the cells in the continuum damage regime and the cells with weak discontinuities.